THE ABILITY OF STUDENTS IN USING ENGLISH CONJUNCTION (CASE STUDY AT SENIOR HIGH SCHOOL SMA NEGERI 5 BANDA ACEH) - Maulizan ZA (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2013)
This research is about the ability of Students in Using EnglishConjunction. The aim of this study is to measure the ability of second year students ofSenior high school in using English conjunctions. The samples of this research were57 second semester students of senior high school. The determination of the sampleswas done randomly. In collecting the data, they were given a set of test inunderstanding the usage of conjunction. The number of items are 40, they weredivided into two parts, the first part (completed the paragraph in using coordinatingand subordinating conjunction) and the second part (complete the sentence in usingcoordinating and subordinating conjunction). In processing data the writer used thestatistical procedure such as, the range score, the interval width, the interval class, thefrequency distribution, and arithmetic mean ( X ). From the data analysis the meanscore of second semester students of senior high school is 60,15. It is considered thecriteria of value in this research is not enough. It is recommended to the researchwhich relates to the ability of second semester students of senior high school in usingconjunctions or other the same level can be continued by other researchers so that theunbreakable problems can be solved in the future.